1389. Pharmacokinetic/Pharmacodynamic (PK/PD) Evaluation of a Novel Aminomethylcycline Antibiotic, KBP-7072, in the Neutropenic Murine Pneumonia Model Against S. aureus (SA) and S. pneumoniae (SPN). (26th November 2018) - Lepak, Alexander J; Zhao, Miao; Liu, Qingmei; Wang, Ping; Wang, Yanli; Bader, Justin C; Ambrose, Paul G; Andes, David R
Abstract: Background: KBP-7072 is a novel aminomethylcycline antibiotic with broad-spectrum activity that includes organisms with drug-resistance to β-lactams and tetracyclines. We examined the PK/PD relationship between KBP-7072 drug exposures and treatment effect using a neutropenic murine pneumonia model against a diverse group of SA and SPN. Methods: Five SAs (three MRSAs) and six SPNs (three PCNs NS, two Tet R ) strains were used. MICs were determined by CLSI Methods. Plasma and ELF PK was determined after SC dosing (range 1–256 mg/kg). Lung burden was assessed by CFU counts at the beginning and end of therapy (24 hours). Infected mice were treated with KBP-7072 by SC route: SA dose range 0.25–64 mg/kg/6 hours, SPN dose range 0.06–16 mg/kg/6 hours. The Emax Hill equation was used to model the dose–response data to the PK/PD index AUC/MIC. The magnitude of the PK/PD index (plasma free and ELF total concentrations) associated with net stasis, 1- and 2-log kill were determined in the pneumonia model for all strains. Results: SA MICs were 0.25 mg/L for all isolates and SPN MICs were 0.008–0.016 mg/L. Plasma PK of KBP-7072 included: Cmax 0.12–25.2 mg/L, AUC0-∞ 1.1–234 mg hour/L, T 1/2 3.2–4.6 h. ELF PK by urea correction methods included: Cmax 0.06–13.3 mg/L, AUC0-∞ 0.4–95 mg hour/L, T 1/2 3.1–4 hours. ELF penetration based on free plasma drug concentrations (77.5% bound) ranged from 82 to 238%. AUC was linear over the dose range ( R 2 = 0.99). Potent dose-dependent cidal activity (3–5 log kill) was observed against all strains. AUC/MIC was a robust predictor of efficacy (SA R 2 = 0.89, SPN R 2 0.80). Median static, 1- and 2-log kill AUC/MIC values are shown in the table. Conclusion: KBP-7072 demonstrated potent in vivo efficacy against SA and SPN, including strains with elevated minocycline MIC and β-lactam resistance, in the neutropenic murine pneumonia model. A 3–5 log kill was observed and AUC/MIC was strongly associated with efficacy. The AUC/MIC target for net stasis was comparable between SA and SPN at a plasma fAUC/MIC target of 1 and ELF AUC/MIC target 2. Cidal targets were similarly very low. All targets were numerically lower than comparative tetracyclines. These results should prove useful for clinical dosing regimen optimization. Disclosures: A. J. Lepak, KBP Biosciences: Research Contractor, Research support. Q. Liu, KBP Biosciences: Employee, Salary. P. Wang, KBP Biosciences: Employee, Salary. Y. Wang, KBP Biosciences: Employee, Salary. J. C. Bader, KBP Biosciences: Research Contractor, Research support. P. G. Ambrose, KBP Biosciences: Research Contractor, Research support. D. R. Andes, KBP Biosciences: Research Contractor, Research support.